The impact of financial leverage on the variance of stock returns - David Yechiam Aharon; Yossi Yagil (International Journal of Financial Studies, 2019)
This paper investigates the direct theoretical relationship between the variance of stock returns (σ2E) and financial leverage (L) considering both corporate and personal taxes. Using a dataset of U.S. industrial firms, we examine the variance of stock returns as a function of the firm's financial leverage. We demonstrate that (1) the variance of stock returns is positively related to the firm's financial leverage, (2) the relationship between the variance of stock returns and financial leverage is positive when corporate and personal taxes are also considered, and (3) with regard to the relationship between the variance of stock returns and financial leverage, using market measures of the latter tends to generate a higher coefficient of determination and a more accurate approximation of the theoretical relationship between financial leverage and the variance of stock returns.
Keywords: G30; G32; 330; volatility; financial leverage; market imperfections; corporate taxes; personal taxes